Genome reprogramming during the first cell cycle in in vitro produced porcine embryos - I. Barnetová; K. Okada (Czech Journal of Animal Science, 2010)
Conflicting data still exist regarding the extent of paternal pronuclear DNA demethylation in one cell-stage mammalian embryos. Demethylation of paternal pronuclear DNA was observed in in vitro produced porcine zygotes, whereas in vitro produced embryos do not show any or only weak paternal genome demethylation. In our experiments, we have used and compared two in vitro techniques commonly used for in vitro embryo production (in vitro fertilization and intracytoplasmic sperm injection) and then we evaluated the extent of labelling in both these groups after 5-methylcytosine (5-MeC) or dimethyl H3/K9 labelling. We have found no differences in the methylation pattern between both those techniques used for the production of embryos. Moreover, we did not detect any demethylation of paternal DNA after 5-MeC labelling at all. Contrary to this, labelling with dimethyl H3/K9 antibodies showed differences in labelling intensity between maternal and paternal genomes in 42% of zygotes after in vitro fertilization and in 44% of zygotes after intracytoplasmic sperm injection. Our results indicate that in vitro matured pig oocytes exhibit rather inconsistent methylation patterns. This inconsistency probably resulted from insufficient cytoplasmic maturation of oocytes and to a lesser extent from the in vitro technique for embryo production.